2021
DOI: 10.33007/inf.v7i2.2681
|View full text |Cite
|
Sign up to set email alerts
|

Kondisi Lanjut Usia Di Indonesia Era Bonus Demografi

Abstract: Saat ini Indonesia sedang memasuki era Bonus Demografi. Namun untuk dapat meraihnya, terdapat tantangan besar yang harus dihadapi yaitu kebutuhan akan kualitas sumber daya manusia yang unggul dan berdaya saing. Hal ini juga menjadi tantangan dalam menyongsong era Bonus Demografi kedua seiring meningkatnya jumlah lanjut usia. Terkait dengan persyaratan tersebut, kajian ini memberikan gambaran kondisi lanjut usia dan capaian parameter demografi provinsi di era Bonus Demografi. Sumber data kajian adalah Survei So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
7
0
3
Order By: Relevance
“…Based on the data from The Statistical bureau, 2017 the proportion of Indonesian older people within 5 decades had increased more than twofolds from 1971 to 2019 period, that is, 4% to 9.6% (25 million). 7,8 The epidemiological study reported that mental illness problems have become a concern among the older population, such as anxiety-related disorders with the presence of physical illness, dementia, functional illnesses due to depression. 9 In addition, the study of mental disorders' prevalence amongst seniors in developing countries is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the data from The Statistical bureau, 2017 the proportion of Indonesian older people within 5 decades had increased more than twofolds from 1971 to 2019 period, that is, 4% to 9.6% (25 million). 7,8 The epidemiological study reported that mental illness problems have become a concern among the older population, such as anxiety-related disorders with the presence of physical illness, dementia, functional illnesses due to depression. 9 In addition, the study of mental disorders' prevalence amongst seniors in developing countries is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Penduduk lanjut usia atau lansia terus mengalami peningkatan seiring kemajuan di bidang kesehatan yang ditandai dengan meningkatnya angka harapan hidup dan menurunnya angka kematian. Dijelaskan bahwa lanjut usia adalah seseorang yang telah mencapai usia 60 (enam puluh) tahun ke atas (Cicih & Agung, 2022). Tahun 2019 diperoleh data yang menunjukkan bahwa terdapat 9,60% lansia di Indonesia dan rasio ketergantungan lansia terhadap penduduk produktif sebesar yaitu 15,01% yang berarti mengalami peningkatan (Badan Pusat Statistik, 2019).…”
Section: Pendahuluanunclassified
“…Toddlers born with low birth weight are a determinant of stunting in toddlers (Kementerian Kesehatan RI, 2016). In addition, mothers who give birth to toddlers with birth spacing that are too close or less than two years are more at risk of experiencing death which can attack both mothers and toddlers (Cicih, 2019).…”
Section: Relationship Between Birth Distance Status and Stunting Inci...mentioning
confidence: 99%